5y-2-4y-3y2-4=4y+2

Rewrite 4 as 22.

5y-2-4y-3y2-22=4y+2

Since both terms are perfect squares, factor using the difference of squares formula, a2-b2=(a+b)(a-b) where a=y and b=2.

5y-2-4y-3(y+2)(y-2)=4y+2

5y-2-4y-3(y+2)(y-2)=4y+2

Finding the LCD of a list of values is the same as finding the LCM of the denominators of those values.

y-2,(y+2)(y-2),y+2

The LCM is the smallest positive number that all of the numbers divide into evenly.

1. List the prime factors of each number.

2. Multiply each factor the greatest number of times it occurs in either number.

The number 1 is not a prime number because it only has one positive factor, which is itself.

Not prime

The LCM of 1,1,1 is the result of multiplying all prime factors the greatest number of times they occur in either number.

1

The factor for y-2 is y-2 itself.

(y-2)=y-2

(y-2) occurs 1 time.

The factor for y+2 is y+2 itself.

(y+2)=y+2

(y+2) occurs 1 time.

The factor for y-2 is y-2 itself.

(y-2)=y-2

(y-2) occurs 1 time.

The factor for y+2 is y+2 itself.

(y+2)=y+2

(y+2) occurs 1 time.

The LCM of y-2,y+2,y-2,y+2 is the result of multiplying all factors the greatest number of times they occur in either term.

(y-2)(y+2)

(y-2)(y+2)

Multiply each term in 5y-2-4y-3(y+2)(y-2)=4y+2 by (y-2)(y+2) in order to remove all the denominators from the equation.

5y-2⋅((y-2)(y+2))-4y-3(y+2)(y-2)⋅((y-2)(y+2))=4y+2⋅((y-2)(y+2))

Simplify 5y-2⋅((y-2)(y+2))-4y-3(y+2)(y-2)⋅((y-2)(y+2)).

Simplify each term.

Cancel the common factor of y-2.

Cancel the common factor.

5y-2⋅((y-2)(y+2))-4y-3(y+2)(y-2)⋅((y-2)(y+2))=4y+2⋅((y-2)(y+2))

Rewrite the expression.

5⋅(y+2)-4y-3(y+2)(y-2)⋅((y-2)(y+2))=4y+2⋅((y-2)(y+2))

5⋅(y+2)-4y-3(y+2)(y-2)⋅((y-2)(y+2))=4y+2⋅((y-2)(y+2))

Apply the distributive property.

5y+5⋅2-4y-3(y+2)(y-2)⋅((y-2)(y+2))=4y+2⋅((y-2)(y+2))

Multiply 5 by 2.

5y+10-4y-3(y+2)(y-2)⋅((y-2)(y+2))=4y+2⋅((y-2)(y+2))

Cancel the common factor of (y-2)(y+2).

Move the leading negative in -4y-3(y+2)(y-2) into the numerator.

5y+10+-(4y-3)(y+2)(y-2)⋅((y-2)(y+2))=4y+2⋅((y-2)(y+2))

Factor (y-2)(y+2) out of (y+2)(y-2).

5y+10+-(4y-3)(y-2)(y+2)(1)⋅((y-2)(y+2))=4y+2⋅((y-2)(y+2))

Cancel the common factor.

5y+10+-(4y-3)(y-2)(y+2)⋅1⋅((y-2)(y+2))=4y+2⋅((y-2)(y+2))

Rewrite the expression.

5y+10-(4y-3)=4y+2⋅((y-2)(y+2))

5y+10-(4y-3)=4y+2⋅((y-2)(y+2))

Apply the distributive property.

5y+10-(4y)–3=4y+2⋅((y-2)(y+2))

Multiply 4 by -1.

5y+10-4y–3=4y+2⋅((y-2)(y+2))

Multiply -1 by -3.

5y+10-4y+3=4y+2⋅((y-2)(y+2))

5y+10-4y+3=4y+2⋅((y-2)(y+2))

Simplify by adding terms.

Subtract 4y from 5y.

y+10+3=4y+2⋅((y-2)(y+2))

Add 10 and 3.

y+13=4y+2⋅((y-2)(y+2))

y+13=4y+2⋅((y-2)(y+2))

y+13=4y+2⋅((y-2)(y+2))

Simplify 4y+2⋅((y-2)(y+2)).

Cancel the common factor of y+2.

Factor y+2 out of (y-2)(y+2).

y+13=4y+2⋅((y+2)(y-2))

Cancel the common factor.

y+13=4y+2⋅((y+2)(y-2))

Rewrite the expression.

y+13=4⋅(y-2)

y+13=4⋅(y-2)

Apply the distributive property.

y+13=4y+4⋅-2

Multiply 4 by -2.

y+13=4y-8

y+13=4y-8

y+13=4y-8

Move all terms containing y to the left side of the equation.

Subtract 4y from both sides of the equation.

y+13-4y=-8

Subtract 4y from y.

-3y+13=-8

-3y+13=-8

Move all terms not containing y to the right side of the equation.

Subtract 13 from both sides of the equation.

-3y=-8-13

Subtract 13 from -8.

-3y=-21

-3y=-21

Divide each term by -3 and simplify.

Divide each term in -3y=-21 by -3.

-3y-3=-21-3

Cancel the common factor of -3.

Cancel the common factor.

-3y-3=-21-3

Divide y by 1.

y=-21-3

y=-21-3

Divide -21 by -3.

y=7

y=7

y=7

Solve for y 5/(y-2)-(4y-3)/(y^2-4)=4/(y+2)